2006
DOI: 10.1007/s00705-005-0708-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel reverse transcription loop-mediated isothermal amplification for rapid detection of foot-and-mouth disease virus

Abstract: Speed is paramount in the diagnosis of foot-and-mouth disease (FMD) and simplicity is required if a test is to be deployed in the field. The development of a one-step, reverse transcription loop-mediated amplification (RT-LAMP) assay enables FMD virus (FMDV) to be detected in under an hour in a single tube without thermal cycling. A fragment of the 3D RNA polymerase gene of the virus is amplified at 65 degrees C in the presence of a primer mixture and both reverse transcriptase and Bst DNA polymerase. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
181
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(187 citation statements)
references
References 17 publications
4
181
0
2
Order By: Relevance
“…During the present study, the application of a constant temperature of 65 °C for 60 min is similar to Dukes et al (14). Moreover, RT-LAMP was found suitable for FMDV serotyping at 63 °C for 60 min; this finding was also reported by Madhanmohan et al (9).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…During the present study, the application of a constant temperature of 65 °C for 60 min is similar to Dukes et al (14). Moreover, RT-LAMP was found suitable for FMDV serotyping at 63 °C for 60 min; this finding was also reported by Madhanmohan et al (9).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the specificity of RT-LAMP was 100% with no cross-reactivity and this was also observed by Madhanmohan et al (9). In contrast to this, Dukes et al (14) evaluated RT-LAMP assay with TaqMan rRT-PCR and reported 81/98 (82.65%) and 94/98 (95.91%) positive by RT-LAMP and rRT-PCR, respectively. However, Dukes et al (14) reported that this may be due to high genetic variation among the FMDV genome.…”
Section: Discussionmentioning
confidence: 55%
“…Gradual depletion of magnesium ion during amplification reaction is the reason behind change of pre-amplification violet colour of reaction mixture to post-amplification sky blue colour in a positive LAMP reaction [6]. DNA intercalating dyes like SYBR green I and picogreen can be used for detecting amplified product [19,20]. But it requires a UV light source for visualisation.…”
Section: Resultsmentioning
confidence: 99%
“…The results of LAMP can be observed directly with the naked eye after adding an intercalating dye and visualised by gel-electrophoresis or real-time fluorogenic analysis with a thermal cycler. LAMP assays have been used in detecting a variety of pathogens, including animal viruses (7,9). A set of four primers targeting conserved segment 1 of BTV RNA was used in an RT-LAMP reaction developed in our laboratory for the detection of BTV genome (30).…”
mentioning
confidence: 99%